Egypt’s new authoritarianism from an institutionalist perspective: formal-informal interactions before and after the Egyptian revolution - Hani Awad (575131) (2022)
Utilizing an institutionalist approach, this paper traces the historical transitions of formal-informal interactions in the Egyptian political system before and after the 2011 Revolution. I argue that formal-informal interactions moved from Complementary during the first two decades of Mubarak’s rule, to Competing in his last decade, then back to Complementary under Sisi. Each transition was motivated by a critical juncture. The first transition was driven by Mubarak’s desire to bequeath power to his son, Gamal, while the second was motivated by the collapse of his regime in 2011. Each transition was marked by differing means. Mubarak used electoral politics to manage formal-informal relations, while the current regime under Sisi is heavily reliant on coercion. Other Information Published in: British Journal of Middle Eastern Studies License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13530194.2022.2113503